Recent progress in optical clearing of eye tissues. (November 2021) - Lu, Wenhan; Pei, Zhenle; Hu, Wei; Tan, Chen; Tong, Xiaoyu; Feng, Yi; Sun, Xinghuai
Abstract: The growing need for viewing the detailed 3D structures of various tissues and organs requires advanced tissue processing and imaging techniques. However, light scattering by tissues hinders detailed structural observations. To overcome this, the emerging technique of "tissue optical clearing" has been flourishing in recent decades, providing excellent opportunities for imaging deep, micro-scale structures of various organs, or even of the whole body. In recent years, advanced tissue clearing techniques have been optimized for specific tissues and organs. Among these tissues, the eye is unique owing to its delicate structure and pigmented retinal epithelial cells, calling for more work on making these tissues "transparent". In this review, we searched Medline and Embase for studies published between January 2006 and August 2021 using the terms "tissue optical clearing", "ophthalmology", "eye", and "optical clearing agents", and we reviewed the publications on the optical clearing techniques of eye tissue from 2006 to the present, including both the clearing procedures and the subsequent analytical processes, thus gaining more insight into the application of tissue optical clearing in basic eye research. Furthermore, we discuss the future potential of optical clearing applications in clinical ophthalmology.